Artificial Intelligence Applications & Venture Funding in Healthcare - Olli Halminen; Henni Tenhunen; Antti Heliste; Timo Seppälä (The Research Institute of the Finnish Economy (ETLA), 2019)
Venture Capital (VC) funding raised by companies producing Artificial Intelligence (AI) solutions is on the rise. In healthcare, VC funding is distributed unevenly and certain technologies have attracted significantly more funding than others. The funding decisions made by VC companies also work as a technology driver for the industry. We analyzed a database of 106 Healthcare AI companies collected from open online sources to understand factors affecting VC funding of AI companies operating in different areas of healthcare. Companies acting as R&D catalysts have been most succesful in raising VC funding. The results suggest that there is a significant connection between higher funding and having research organizations and pharmaceutical companies as the customer of the product or service. In addition, focusing on AI solutions that are applied to direct patient care delivery is associated with lower funding. We discuss the implications of our findings on health technology research and development, and on the barriers of platform data markets in healthcare industry.
Keywords: G2; G24; I1; I19; 330; Artificial Intelligence; Capital Funding; Technology